Posterior-Only Sagittal Correction in Degenerative Lumbar Kyphosis Using Posterior Interpedicular Osteotomy (PIO) and Bilateral Discectomy with Hyperlordotic Cages: A Retrospective Case Series - Andrea Franchini; Giuseppe Rovere; Felice Barletta; Franco Lucio Gorgoglione; Giovanni Noia; Giuseppe Maccagnano; Andrea Perna (Journal of Personalized Medicine, 2026)
Introduction: Degenerative lumbar kyphosis (DLK) is a common cause of sagittal imbalance, pain, and functional disability. While three-column osteotomies provide powerful correction, they are associated with substantial morbidity. We evaluated the radiographic and clinical outcomes of a novel posterior-based correction strategy combining Posterior Interpedicular Osteotomy (PIO), bilateral discectomy, and hyperlordotic transforaminal lumbar interbody fusion (TLIF) in patients with DLK. Materials and Methods: A retrospective single-center case series was conducted including 215 consecutive patients with symptomatic DLK and pelvic incidence–lumbar lordosis (PI–LL) mismatch >10° treated between 2019 and 2023. All patients underwent PIO combined with bilateral discectomy and insertion of a 20° hyperlordotic TLIF cage. Radiographic parameters, including lumbar lordosis (LL), pelvic tilt (PT), and sacral slope (SS), were assessed preoperatively and up to 24 months postoperatively. Clinical outcomes were evaluated using the Visual Analog Scale (VAS), Oswestry Disability Index (ODI), and Short Form-36 (SF-36). Complications were systematically recorded. Results: Mean lumbar lordosis improved from 15.7° ± 8.3° preoperatively to 45.4° ± 11.6° at 24 months, corresponding to a mean correction of 29.7° ± 10.1° and 12.4° ± 2.9° per treated level (p < 0.001). Significant improvements were observed in PT, SS, VAS, ODI, and SF-36 scores (all p < 0.001), with maintenance of correction throughout follow-up. Mean operative time was 218.4 ± 47.3 min and mean blood loss was 483.2 ± 195.7 mL. The overall complication rate was 16.3%, with incidental durotomy being the most common event (14.9%). No cases of cage migration, deep infection, neurological deterioration, or radiographic pseudarthrosis were identified among patients who underwent CT evaluation. Conclusions: PIO combined with bilateral discectomy and hyperlordotic TLIF achieved substantial and durable sagittal correction with significant clinical improvement and an acceptable safety profile. By combining extensive posterior release with preservation of the anterior tension band, this technique may represent an effective intermediate alternative between conventional posterior column osteotomies and more invasive three-column deformity correction procedures.